2018
DOI: 10.3389/fncel.2017.00430
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial-Supported Cell Transplantation Treatments for Spinal Cord Injury: Challenges and Perspectives

Abstract: Spinal cord injury (SCI), resulting in para- and tetraplegia caused by the partial or complete disruption of descending motor and ascending sensory neurons, represents a complex neurological condition that remains incurable. Following SCI, numerous obstacles comprising of the loss of neural tissue (neurons, astrocytes, and oligodendrocytes), formation of a cavity, inflammation, loss of neuronal circuitry and function must be overcome. Given the multifaceted primary and secondary injury events that occur with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 211 publications
1
69
0
2
Order By: Relevance
“…More recent strategies for treatment have taken advantage of advances in tissue engineering and stem cell technologies, as well as increased understanding of SCI pathobiology to encourage axonal regeneration through the native environment of the spinal cord. These include the use of cell-seeded or acellular scaffolds [10], administration of pharmacologic or antibody-based inhibitors of regeneration-inhibiting pathways to encourage regeneration and/or sprouting of axon collaterals [11,12], electrical rewiring strategies that take advantage of the innate ability of circuits within the spinal cord to execute sensory and motor tasks, and enhance this ability with an electrochemical strategy comprising lumbosacral electrical stimulation and systemic administration of serotonin and dopamine receptor agonists [13][14][15] and generation of new neurons with stem cell-based approaches (reviewed in [16]). Functional recovery has been demonstrated in human patients with SCI implanted with olfactory ensheathing cells in the injury site in the presence of a nerve graft for support [17,18].…”
Section: Treatment Strategies For Scimentioning
confidence: 99%
“…More recent strategies for treatment have taken advantage of advances in tissue engineering and stem cell technologies, as well as increased understanding of SCI pathobiology to encourage axonal regeneration through the native environment of the spinal cord. These include the use of cell-seeded or acellular scaffolds [10], administration of pharmacologic or antibody-based inhibitors of regeneration-inhibiting pathways to encourage regeneration and/or sprouting of axon collaterals [11,12], electrical rewiring strategies that take advantage of the innate ability of circuits within the spinal cord to execute sensory and motor tasks, and enhance this ability with an electrochemical strategy comprising lumbosacral electrical stimulation and systemic administration of serotonin and dopamine receptor agonists [13][14][15] and generation of new neurons with stem cell-based approaches (reviewed in [16]). Functional recovery has been demonstrated in human patients with SCI implanted with olfactory ensheathing cells in the injury site in the presence of a nerve graft for support [17,18].…”
Section: Treatment Strategies For Scimentioning
confidence: 99%
“…Bioengineering strategies capable of simultaneously providing differentiation signals and responding to exogenous signals offer tremendous promise for regenerative medicine (more comprehensive reviews can be found in [ 44 , 45 , 46 , 47 , 48 , 49 ]). Further, biomaterial conduits can represent a physical barrier between encapsulated cells and host immune response [ 50 ] until these cells can adapt to their new environment and respond to the existing chemical and physical cues favorably.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 3D printing can be implemented to fabricate complex free-form anatomical shapes for prosthetic limbs and surgical implants. In recent years, this approach has been progressed to include the transplantation of cells along with supporting scaffolds and biomolecules for the restoration of pathologically altered tissue architectures (Liu et al, 2017). The scaffolds need to mimic the native tissue structure and provide comparative analogs of the extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%